Environmental terrestrial gamma radiation dose-rate and its relationship with soil type and underlying geological formations in Kota Tinggi district, Malaysia / Ahmad Taufek Abdul Rahman, Ahmad Termizi Ramli and Ahmad Lufti Abdul Rahman - Abdul Rahman, Ahmad Taufek; Ramli, Ahmad Termizi; Abdul Rahman, Ahmad Lutfi (2004)
The terrestrial gamma radiation level was determined covering the Kota Tinggi district of Peninsular Malaysia. The dose-rate was measured at 748 locations using gamma ray detector system consisting of a 2.54 cmx2.54 cm Nal (TI) as a gamma detector. Results have allowed construction of a terrestrial gamma ray isodose contour map of Kota Tinggi district. The relationships between the gamma radiation dose level measured at various locations and the soil type and underlying geological are discussed. The highest terrestrial gamma dose-rate measured is 630 ± 63 nGy h-1 and the lowest terrestrial gamma dose-rate measured is 45 ± 5 nGy h-1.